Teaching Reading Comprehension in English in a Distance Web-Based Course: New Roles for Teachers - Jorge Hugo Muñoz Marín; Adriana González Moncada (Universidad Nacional de Colombia, 2010)
Distance web-based learning is a popular strategy in ELT teaching in Colombia. Despite of the growth of experiences, there are very few studies regarding teachers' participation in these courses. This paper reports preliminary findings of an on-going study aiming at exploring the roles that a teacher plays in an efl reading comprehension distance web-based course. Data analysis suggests that teachers play new roles solving technical problems, providing immediate feedback, interacting with students in a non traditional way, providing time management advice, and acting as a constant motivator. The authors conclude that EFL teachers require training for this new teaching roles and the analysis of web-based distance learning environments as an option under permanent construction that requires their active participation.